NDPBridge: Enabling Cross-Bank Coordination in Near-DRAM-Bank Processing Architectures - Tian, Boyu; Li, Yiwei; Jiang, Li; Cai, Shuangyu; Gao, Mingyu (2024 ACM/IEEE 51st Annual International Symposium on Computer Architecture (ISCA), 2024)
Various near-data processing (NDP) designs have been proposed to alleviate the memory wall challenge for data-intensive applications. Among them, near-DRAM-bank NDP architectures, by incorporating logic near each DRAM bank, promise the highest efficiency and have already been commercially available now. However, due to physical isolation, fast and direct cross-bank communication is impossible in these architectures, limiting their usage to only simple parallel patterns. Applications may also suffer from severe load imbalance if each bank contains data with diverse computation loads. We thus propose NDPBridge, with novel hardware-software co-design to enable cross-bank communication and dynamic load balancing for near-bank NDP systems. We introduce hardware bridges along the DRAM hierarchy to coordinate message transfers among banks. The hardware changes are constrained and do not disrupt the existing DDR links and protocols. We further enable hierarchical and data-transfer-aware load balancing, built upon the above hardware communication path and a task-based programming model. The data transfer overheads are minimized with several novel optimizations to hide latency, avoid congestion, and reduce traffic. Our evaluation shows that NDPBridge significantly outperforms existing NDP designs by 2.23 × to 2.98 × on average.